Peran Tutor dalam Mengatasi Kesulitan Belajar Matematika Peserta Didik Program Paket A di PKBM Cerdas Mandiri - Liza Arisna Rahman (Jurnal Aktual Pendidikan Indonesia, 2025)
This study aims to describe the role of tutors in overcoming students’ learning difficulties in mathematics at the Package A Program of PKBM Cerdas Mandiri. The research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The subjects of this study were tutors and students enrolled in the Package A Program. The findings show that learning difficulties in mathematics are mainly caused by students’ low motivation, limited conceptual understanding, and monotonous teaching methods. To address these challenges, tutors implement various efforts such as applying active and engaging learning models, using concrete learning media, encouraging students to ask questions, and providing remedial sessions for those who do not meet the minimum learning standards. The use of concrete media significantly helps students understand mathematical concepts more effectively, especially for those who are still in the concrete operational stage of thinking. However, several obstacles remain, including the limited availability of learning media, inadequate learning facilities, and low student engagement. Therefore, tutors are expected to be more creative in developing contextual learning media and collaborate with parents and institutions to create a more supportive learning environment. Overall, the success in overcoming mathematical learning difficulties depends on the collaboration between tutors, students, and the educational institution